Driving Performance in Construction: Innovation’s Role in Entrepreneurial Orientation and Dynamic Capabilities - Neni Dyah Purwanti; Avanti Fontana (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In a dynamic business environment, construction firms are required to innovate and adapt to enhance organizational performance. This study aims to analyze the direct and indirect effects of entrepreneurial orientation and dynamic capabilities on organizational performance through the innovation process as a mediating variable among construction service providers at Perum Jasa Tirta II. The research adopts a quantitative approach with a cross-sectional design, involving 89 companies selected through purposive sampling. Data were collected via an online questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares. The findings reveal that entrepreneurial orientation and dynamic capabilities positively and significantly influence the innovation process and organizational performance, with the innovation process mediating these relationships. However, the innovation process does not have a significant direct effect on organizational performance, indicating the need for effective implementation. This study is limited to the context of Perum Jasa Tirta II, suggesting further research for broader generalization. The study concludes that construction firms should foster entrepreneurial culture and adaptive capabilities to drive innovation and enhance performance, particularly in competitive public construction projects.